Genotype of congenital adrenal hyperplasia patients with testicular adrenal rest tumor - GÜRAN, TÜLAY (My University, 2022)
Testicular adrenal rest tumor (TART) is one of the important complications that can cause infertility in male patients with congenital adrenal hyperplasia (CAH) and should therefore be diagnosed and treated at an early age. The factors that result in TART in CAH have not been completely understood. The aim of this study is to evaluate the genotype-phenotype correlation in CAH patients with TART.Method: Among 230 malepatients with CAH who were followed upwith regular scrotal ultrasonography in 11 different centers in Turkey, 40 patients who developed TARTand whose CAH diagnosis was confirmed by genetic testing were included in this study. Different approaches and methods were used for genotype analysis in this multicenter study. A few centers first screened the patients for the ten most common mutations in CYP21A2 and performed Sanger sequencing for the remaining regions only if these prior results were inconclusive while the majority of the departments adopted Sanger sequencing for the whole coding regions and exon-intron boundaries as the primary molecular diagnostic approach for patients with either CYP21A2 orCYP11B1 deficiency. The age of CAH diagnosis and TART diagnosis, type of CAH, and identified mutations were recorded.Results: TART was detected in 17.4% of the cohort [24 patients with salt-wasting (SW) type, four simple virilizing type, and one with nonclassical type with 21-hydroxylase (CYP21A2) deficiency and 11 patients with 11-beta hydroxylase (CYP11B1) deficiency]. The youngest patients with TART presenting with CYP11B1 and CYP21A2 deficiency were of 2 and 4 years, respectively. Eight different pathogenic variants in CYP21A2were identified. The most common genotypes were c.293-13C>G/c.293-13C>G (31%) followed by c.955C>T/ c.955C>T(27.6%) and c.1069C>T/c.1069C>T (17.2%). Seven different pathogenic variants were identified in CYP11B1. The most common mutation in CYP11B1 in our study was c.896T>C (p.Leu299Pro).Conclusion: We found that 83% TART patients were affected with SW typeCYP21A2 deficiency,and the frequent mutations detected were c.955C>T (p.Gln319Ter), c.293-13C>G in CYP21A2 and c.896T>C (p.Leu299Pro) inCYP11B1. Patients with CYP11B1 deficiency may develop TART at an earlier age. This study that examined the genotype-phenotype correlation in TART may benefit further investigations in larger series.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; GENETİK VE KALITIM; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik (klinik); Moleküler Biyoloji; Genetik; Genetics (clinical); Molecular Biology; Genetics; Testicular adrenal rest tumor; Congenital adrenal hyperplasia; Genotype-phenotype correlation; ADULT MALES; CYP21A2 MUTATIONS; TURKISH PATIENTS; CYP11B1; PREVALENCE; DEFICIENCY; ADOLESCENT; GENETICS; OUTCOMES; Testicular adrenal rest tumorCongenital adrenal hyperplasiaGenotype-phenotype correlation